Preferred Working Time Models and Equal Opportunities in Gynecology and Obstetrics: Results of the Systematic Trinational FARBEN Survey Favorisierte Arbeitszeitmodelle und Gleichberechtigung in der Gynakologie und Geburtshilfe: die Ergebnisse der systematischen trinationalen FARBEN-Umfrage - Tauber, Nikolas; Amann, Niklas; Foessleitner, Philipp; Klee, Amanda; Becker, Claudia; Kiblawi, Rama; Göpfert, Martin; Kiessling, Nora; Taumberger, Nadja; Beizermann, Evelin; Krawczyk, Natalia; Simowitsch, Solveig; et al. (Geburtshilfe und Frauenheilkunde, 2025)
Introduction The trinational survey project conducted by the Young Forums of the German, Austrian, and Swiss Societies for Gynecology and Obstetrics aims to assess the preferences of prospective and practicing gynecologists regarding various work-time models, the compatibility of family and career, as well as parental leave. Materials and Methods Between October 2023 and May 2024, a total of 1364 participants took part in the survey. The questionnaire consisted of 62 questions covering topics such as the workplace in general, work-time models, training priorities, team compositions, and professional goals. Participation was voluntary and anonymous. Results Of the 1364 participants, 75.3% were employed in Germany, 12.9% in Austria, and 11.8% in Switzerland. Men were significantly more likely to aspire to a chief physician position compared to women (26.5% vs. 3.6%; p < 0.001). Only 12.5% of participants overall preferred full-time employment, although 63.0% of residents worked full-time. Additionally, 65.4% of respondents stated that their workplace did not provide childcare with flexible hours. At the same time, 76.0% valued workplace-proximate childcare as an important factor in choosing an employer. Conclusions The results highlight heterogeneous and individual needs and priorities among all (prospective) gynecologists. At a time when individuality and equality are becoming increasingly significant, it is essential to promote work environments that meet the demands and needs of all physicians. The results should therefore be critically discussed to implement potential adjustments and improvements in practice.
CRIS-Team Scopus Importer:2025-03-14
Keywords: career goals; equal opportunities; gender differences; online survey; working time models